Chevon production and quality of Kalahari Red goats fed increasing levels of hempseed cake substituted for soybean meal. (May 2022) - Semwogerere, Farouk; Chikwanha, Obert C.; Katiyatiya, Chenaimoyo L.F.; Marufu, Munyaradzi C.; Mapiye, Cletos
Abstract: A 42-d study was conducted to evaluate the effects of replacing soybean meal with increasing levels of hempseed cake (HSC) in goat finishing diets on growth performance, carcass and chevon quality attributes. Thirty-five, 3-month-old Kalahari Red wethers (25 ± 1.5 kg initial body weight) were randomly allocated to one of five dietary treatments with seven animals per treatment. Wethers were fed maize-lucerne based finishing diets with inclusions of 0 (control), 25, 50, 75 and 100 g/kg DM of HSC replacing soybean meal as the main protein source. Diet had no effect ( P  > 0.05) on daily feed intake, average daily gain, final body weight and income-over-feed costs. Carcass and meat quality attributes were not influenced ( P  > 0.05) by HSC, except intramuscular fat, which increased linearly ( P  ≤ 0.05) with HSC inclusion levels. It was concluded that HSC could completely replace soybean meal in goat finishing diets without affecting chevon production and quality. Highlights: Growth performance of goats did not differ with inclusion of hempseed cake (HSC). Dietary inclusion of HSC had no effect on goat carcass attributes. Physical meat quality traits were not influenced by addition of HSC in goat diets. Intramuscular fat linearly increased with the inclusion of HSC in goat diets.